Analisis Karakter dan Nilai-Nilai Generasi Z Terhadap Keanggotaan Serikat Pekerja di Perusahaan - Lagandhy, Langga; Anugrah, Rut Gloria (Syntax Corporation, 2026)
This study aims to analyze the challenges and opportunities faced by trade unions in increasing the participation of Generation Z (Gen Z) as union members in companies. Gen Z, born between 1996-2012, has unique characteristics that differ from previous generations, including digital technology proficiency, high social awareness, and an orientation to work-life balance. The research method uses a qualitative approach with a case study at PT LEN Industri. The results of the study show that the main challenges faced by unions include the individualistic attitude of Gen Z, lack of effective socialization, and the negative stigma against unions as organizations that conflict with management. The study found that Gen Z tends to prioritize individual career development and avoid involvement in organizations that are perceived to hinder their career progress. Recommended strategies to increase Gen Z participation include: (1) effective digital socialization through social media platforms and webinars; (2) the implementation of a structured cadre regeneration program that focuses on the development of leadership skills; (3) anti-stigma campaigns with management to change negative perceptions; and (4) providing incentives in the form of training and skill development. This research makes a practical contribution to trade unions in designing recruitment strategies that are more adaptive and relevant to Gen Z's values and preferences, so that unions can maintain their relevance in the digital age and remain effective in fighting for workers' rights.